Optimalisasi Peran BMT Al-Ishlah Kota Jambi Dalam Pemberdayaan Ekonomi UMKM - Saprianto Saprianto; Agustina Mutia; Ahmad Syahrizal (CV. Aksara Global Akademia, 2024)
The purpose of this study was to determine the role of BMT Al-Islah Jambi City in empowering the MSME economy, the obstacles faced by BMT Al-Ishlah Jambi City in carrying out its role in empowering the MSME economy and the efforts made by BMT Al-Ishlah Jambi City in dealing with these obstacles. This type of research is qualitative with a descriptive approach, and the methods used in data collection are observation, interviews and documentation. The subjects in this study were the BMT and its customers. The number of subjects in this study were 10 people. The results of the study show that BMT Al-Ishlah plays a role in developing an entrepreneurial spirit for its customers. Factors that become obstacles faced are limited capital so that BMT has not been able to provide large-scale financing, lack of human resources, and financial literacy of MSMEs is still lacking because customers are only limited to recording business financial receipts and expenditures without supporting document storage. The solution provided by BMT is that we hold group meetings and continue sharing about the constraints of their business. And every week teaches making financial reports so that customers understand where money is coming in and out.